Solitary Crossed Renal Ectopia: Concurrence of Posterior Urethral Valve and Hypospadias. (18th June 2015) - Bagheri, Amin; Khorramirouz, Reza; Keihani, Sorena; Fareghi, Mehdi; Kajbafzadeh, Abdol-Mohammad
Abstract : Solitary crossed renal ectopia (SCRE) represents an exceedingly rare congenital disorder. Although skeletal and genitourinary abnormalities most commonly accompany this condition, vesicoureteral reflux (VUR) has been described in only a few cases. Here, we present two unique cases of SCRE complicated by high-grade VUR concomitant with posterior urethral valve in one case and hypospadias in the other one. We also provide a brief review of the literature on this subject.